Marketing and Communication Strategies of the Accor Group on the European Market, Suggestions for Improvement - Straub, Mia Valentina (2025)
This thesis critically assesses the marketing and communication strategies used by the Accor Group in the European hospitality market. It focuses on how the company structures its brand positioning, digital engagement, and regional marketing approaches, and explores the balance between global consistency and local adaptation. The research combines theoretical models such as the STP framework (Segmentation, Targeting, Positioning), the Marketing Mix, and Integrated Marketing Communication (IMC) with qualitative data collected through interviews with Accor representatives and consumers. The findings show that Accor’s tiered brand structure, strategic partnerships, and digital innovation contribute to its competitive advantage. However, areas such as personalization and sustainability messaging reveal opportunities for further improvement. Based on these findings, the thesis provides practical recommendations to better align Accor’s strategies with regional consumer preferences and strengthen long-term brand engagement.